Characterization of Thirty Cultivars of Mangifera indica L. (Anacardiaceae) by Their Foliar Anatomical Traits - Bhavna Girish SHARMA; Susy ALBERT; Haresh Kumar DHADUK (Notulae Scientia Biologicae, 2018)
Leaves of thirty cultivars of Mangifera indica L. were investigated to compare their anatomical variations and identify the characteristic features which are potential markers for the identification of the cultivars. Variations were noted in the thickness of cuticle, length of epidermal cells in the abaxial and adaxial surfaces, length of palisade and spongy tissue. The length of epidermal cell varied from 10 µm in ‘Goto’ to 25 µm in ‘Desi’ cultivars on adaxial side, while on the abaxial side it varied from 15.5 µm in ‘Alphonso’ to 6.9 µm in ‘Sopari’. The palisade tissue length was maximum in ‘Jahangir’ (111.36 µm), while it was lowest in ‘Fazli’ (24.13 µm). Spongy tissue length was the highest in ‘Jamadar’ (199.92 µm) and lowest in ‘Fazli’ (90.55 µm). Two layers of palisade tissue were seen in ‘Sindoria’, ‘Jhumakhiya 2’, ‘Aambadi’, ‘Neelam’,  ‘Rajapuri’, ‘Fazli’, ‘Jahangir’, ‘Kaju’, and ‘Aamir pasand’, while three layers were seen in ‘Alphonso’, ‘Jamadar’, ‘Ladvo’, ‘Sopari’ and ‘Dudhpendo’. Such parameters can be used for distinctly differentiating varieties among them and thus have an exact identification when morphological features are indistinguishable.